2022
DOI: 10.3390/foods11162536
|View full text |Cite
|
Sign up to set email alerts
|

Development of Saturated Fat Replacers: Conventional and Nano-Emulsions Stabilised by Lecithin and Hydroxylpropyl Methylcellulose

Abstract: The combination of two emulsifiers, lecithin and hydroxypropyl methylcellulose (HPMC), into emulsions is an interesting strategy to design fat replacers in food matrices. The objective of this study was to investigate the effect of HPMC type and concentration on the formation, stability, and microstructure of conventional emulsions and nanoemulsions. Two different types of HPMC with low and high content of methyl and hydroxypropyl groups (HPMC-L and HPMC-H) were evaluated. The results showed that the molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…The replacement of butter with the CNE led to dough pieces (D-CNE) with significantly higher ( p < 0.05) hardness values than the D-control. Although in a previous study, the authors reported similar firmness values for CNE and butter at similar concentrations 39 . The reduction of the fat content in the system may have hindered some of the main functionalities of fat in a dough system, principally lubrication and aeration 5 .…”
Section: Resultsmentioning
confidence: 55%
See 4 more Smart Citations
“…The replacement of butter with the CNE led to dough pieces (D-CNE) with significantly higher ( p < 0.05) hardness values than the D-control. Although in a previous study, the authors reported similar firmness values for CNE and butter at similar concentrations 39 . The reduction of the fat content in the system may have hindered some of the main functionalities of fat in a dough system, principally lubrication and aeration 5 .…”
Section: Resultsmentioning
confidence: 55%
“…Moreover, the rheological properties of the nanoemulsions stabilised by HPMC and lecithin could also explain the spreadability of the dough during baking. In a previous study the rheological behaviour during micro-baking was studied 39 ; at low temperatures (20–40 °C) conventional emulsions and nanoemulsions stabilised by HPMC and lecithin showed a decrease in moduli values, which was related to a weakening effect in the intermolecular hydrogen bonds caused by the increased temperature. Then as temperature increased (40–65 °C), G’ and G” moduli increased, marking the starting point of the gelation temperature, during which the formation of strong hydrophobic interactions between HPMC molecules for the formation of a three-dimensional network took place 39 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations